2007
DOI: 10.2134/agronj2006.0339
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Model Bias and Variability when Calculating Economic Optimum Rates of Nitrogen Fertilization for Corn

Abstract: Efforts to calculate economic optimum rates (EORs) of N fertilization for corn (Zea mays L.) have been hampered by a lack of methods for disaggregating problems caused by model bias and variability in crop responses to N. We illustrate how the concepts of ex post and ex ante analyses can be used in a multistep procedure to disaggregate these problems when calculating ex post EORs when large amounts of data are available. Five models were used to describe yield responses from a collection of 54 small-plot trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…7 and 10). Several past studies showed how the choice of functional forms or response models affects the uncertainty in EONR values for individual trials (Cerrato and Blackmer, 1990;Bullock and Bullock, 1994;Kyveryga et al, 2007).…”
Section: A Framework For Improving Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 10). Several past studies showed how the choice of functional forms or response models affects the uncertainty in EONR values for individual trials (Cerrato and Blackmer, 1990;Bullock and Bullock, 1994;Kyveryga et al, 2007).…”
Section: A Framework For Improving Nitrogenmentioning
confidence: 99%
“…Metadata analysis is the basis for the evidence that is then used to guide decisions. Kyveryga et al (2007) fitted with the seven yield response functions, namely, linear plateau (LP), quadratic (QD), quadratic plateau (QDP), square root quadratic (SRQ), spherical plateau (SPP), exponential (EX), and exponential plateau (EXP). Also shown are the computed economically optimal nitrogen rates (EONR) for each response function and their 68% confidence bands relative to the abscissa.…”
Section: A Framework For Improving Nitrogenmentioning
confidence: 99%
“…Data from the trials are fitted to several statistical models to describe relationships between N rates and yields, and solving the models to identify the economic optimum rates (EORs) (Kyveryga et al, 2007). The economic optimum rate is arrived at the point where the marginal cost (MC) of the fertilizer is equal to the marginal revenue (MR) per unit fertilizer (MC=MR) (Kiprono et al, 2010;Kyveryga et al, 2007). The EORs can differ with the growing conditions, locations and the clones and hence, it is important to consider the factors in the local environment that may influence production.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the economic benefi ts calculated in Table 4 were not aff ected by the shape of N yield response curves, which are oft en estimated for a wide range of N rates applied in small-plot experiments (Kyveryga et al, 2007). It has been proven that discontinuous N yield response curves (with yield plateaus) will likely show lower potential economic benefi ts from VRN applications than those without yield plateaus (Brennan et al, 2007).…”
Section: Economic Benefi Ts and Fertilizer Savingmentioning
confidence: 90%
“…An ideal approach would be to apply a wide range of N fertilizer rates over a large area of soils, estimate site-specifi c N yield response functions, and to calculate EONRs for many small areas within fi elds (Bullock and Lowenberg-DeBoer, 2007;Hurley et al, 2004;Schmidt et al, 2007). One practical challenge is that farmers are generally uncomfortable with yield losses from applying extremely low N rates or for residual fertilizer eff ects from applications of both extremely low and high N rates (Kyveryga et al, 2007). Second, conducting spatial analysis and testing for statistically signifi cant interactions between the eff ect of N and site-specifi c soil characteristics on corn yield have not yet become a mainstream procedure for practicing agronomists.…”
mentioning
confidence: 99%